Direct network externalities and dynamics of two-sided platforms - Fatma Aslan; Chourouk Haouel; Andras Nemeslaki; Robert Somogyi (International Telecommunications Society (ITS), 2021)
We investigate the effect of direct network externalities on the long- run dynamics of two-sided platforms. Two-sided platforms have been widespread in the economy, acting as intermediaries connecting two dis- tinct groups of agents. A defining characteristic of the two-sidedness is the existence of indirect network externalities between the two sides. How- ever, direct externalities can also be important in one or both sides of the market. For instance, direct externalities include review systems where buyers on the platform benefit from other buyers' ratings and comments. We find that considering direct externalities changes the dynamics quali- tatively. For example, instead of saddle path dynamics, they can lead to unstable node dynamics and the collapse of a platform.
Keywords: 330